Design and fabrication of 2-in-1 convertible chair-ladder - Roslan, Arif Haiqal; Mohd Hamami, Mohd Ghazali (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This project introduces a practical solution for optimizing workspace in workshops by designing and fabricating a 2-in-1 convertible chair-ladder. Workshops often struggle with clutter and limited space, which can lead to stress and inefficiency. This innovative product combines the functionality of a chair and a ladder into one compact design. As a chair, it offers comfortable seating, and as a ladder, it provides a stable platform for reaching elevated areas. Built with durable materials and designed with safety and ergonomics in mind, this chair-ladder not only saves space but also simplifies tasks, making it a versatile and cost-effective addition to any workshop.